"We Are Not a Token!": Cultural Citizenship and Transformational Resistance in Higher Education. (September 2022) - Deeb-Sossa, Natalia; Boulware, Janet
Based on ethnographic and archival research, we explore how 10 students asserted their rights to belong and secure a space where they felt safe at UC Davis. We examine the activities and practices of 10 undergraduate Chicanxs and Latinxs students: members of "Radical Academics for Pedagogy" (RAP) and RESISTENCIA. Our interest lies on examining how they enacted cultural citizenship—a process by which they defined themselves, interpreted their histories, constructed their own symbols and political rhetoric, and claimed rights through speeches, actions, cultural discourses, and dialogues. We contend that the students challenged the definitions of belonging and citizenship at UC Davis.